The doctrine of reconciliation ; part 1 - Barth, Karl, 1886-1968; Torrance, Thomas Forsyth, 1913-; Bromiley, Geoffrey William (Edinburgh, Scotland T and T Clark, 1956)
Includes indexes.
Original German ed. : Die Kirchliche Dogmatik, IV : Die Lehre von der Versohnung, 1
Keywords: Reconciliation; Justification (Christian theology).